CVD-grown monolayer graphene induces osteogenic but not odontoblastic differentiation of dental pulp stem cells. Issue 1 (January 2017) - Xie, Han; Chua, Melissa; Islam, Intekhab; Bentini, Ricardo; Cao, Tong; Viana-Gomes, José Carlos; Castro Neto, Antônio Hélio; Rosa, Vinicius
Abstract: Objective: The objective was to investigate the potential of graphene (Gp) to induce odontogenic and osteogenic differentiation in dental pulp stem cells (DPSC). Methods: Gp was produced by chemical vapor deposition. DPSC were seeded on Gp or glass (Gl). Cells were maintained in culture medium for 28 days. Every two days, culture medium from Gp was used to treat cells on Gl and vice versa. Mineralization and differentiation of DPSC on all substrates were evaluated after 14 and 28 days by alizarin red S staining, qPCR, immunofluorescence and FACS. Statistics were performed with two-way ANOVA and multiple comparisons were performed using Tukey's post hoc test at a pre-set significance level of 5%. Results: After 14 and 28 days, Gp induced higher levels of mineralization as compared to Gl. Odontoblastic genes (MSX-1, PAX and DMP) were down-regulated and osteogenic genes and proteins (RUNX2, COL and OCN) were significantly upregulated on Gp comparing to Gl ( p  < 0.05 for all cases). Medium from Gp induced downregulation of odontoblastic genes and increased bone-related gene and protein on Gl. Significance: Graphene induced osteogenic and not odontoblastic differentiation of DPSC without the use of chemical inducers for osteogenesis. Graphene has the potential to be used as a substrate for craniofacial bone tissue engineering research.